(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective The objective is to increase the level of coordination abilities of schoolchildren diagnosed with myopia. Methods The study was conducted in the period from September 2022 to June 2023 at secondary school number 13 in the Kirov region. A group (n=21) of 4th grade students was formed to conduct a pedagogical experiment. These are boys and girls aged 10-11 years with a mild degree of myopia (up to 3 diopters) – myopia of the first degree. The level of development of coordination abilities was determined by a 3x10 meter Shuttle run, a long jump from a place with the right and left sides, Balance on 1 leg and Dynamic coordination of movements. The Student’s T-Test was the main method of mathematical statistics. Results After the end of the pedagogical experiment, the performance of children from the experimental group improved in all indicators. In the shuttle run test, the indicators became higher from 9.36±0.16 to 8.72±0.09 (p<0.05), an increase of 6.8%. The long jump with the right side increased by 10.4% (p<0.05), and with the left side by 7.3% (p<0.05). In the balance on one leg test, the indicators became 13.3% higher (p<0.05), and in the dynamic coordination test, the indicators improved from 8.83±0.89 to 10.05±0.16 (p<0.05), the increase in indicators was 13.8%. Conclusion The results obtained allow us to conclude that our proposed method of using general developmental exercises with objects as a means of developing coordination abilities in children 9-10 years old diagnosed with myopia is effective, which is achieved through regular use of exercises in physical education lessons, as well as by stabilizing the course of myopia during the school day. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 507-513